Spanish Consensus Statement: Clinical Management and Treatment of Tendinopathies in Sport. Issue 10 (19th October 2017) - ,; Fernandez-Jaén, Tomas; Rey, Guillermo Álvarez; Angulo, Francisco; Cuesta, Jordi Ardevol; Loureda, Rafael Arriaza; España, Fernando Ávila; Ayala, Juan; Matas, Ramón Balius; Pazos, Fernando Baró; de Dios Beas Jiménez, Juan; Rosell, Jorge Candel; et al.
On October 15, 2016, experts met at Clínica CEMTRO in Madrid, Spain, under the patronage of the Spanish Society for Sports Traumatology (SETRADE), the Spanish Society of Sports Medicine (SEMED), the Spanish Association of Medical Services for Football Clubs (AEMEF), the Spanish Association of Medical Services for Basketball Clubs (AEMB), F.C. Barcelona, and Clínica CEMTRO. The purpose was to consider the most appropriate clinical management and treatment of tendinopathies in sports, based on proven scientific data described in the medical literature as well as on each expert's experience. Prior to the meeting, each expert received a questionnaire regarding clinical management and treatment of tendinopathies in sports. The present consensus document summarizes the answers to the questionnaire and the resulting discussion and consensus regarding current concepts on tendinopathies in sports.